Muḥammad is not the father of any of your men : the making of the last prophet - Powers, David Stephan (Divinations., 2009)
David Powers claims that the need for Muhammad to be the "seal of all prophets," combined with the fact that Muhammad apparently had an adopted son, Zayd, created a situation that drove early transmitters of the Qur'an to introduce a group of interrelated deletions, additions, and emendations into certain passages of the text.